Industrial Organization - Caves, Richard E.; Uekusa, Masu; Industries - Japan (Washington, D.C Brookings Institution, 1976)
This book makes extensive comparisons between the Japanese and American industrial systems which finds that the economic forces in Japanese industry are similar to those in Western industrial countries.
osa;29/6/17
Loans
Keywords: Big business; Industrial efficiency; Big business - - Japan; Economic conditions - Japan